الاختصاص القضائي الدولي المختلط - عيسى, أ.د. حسين عبدعلي; محمود, د. شيروان علي (Sulaimani Journal for Humanities, 2021)
This research deals with studying the jurisdiction of the mixed court for East Timor currently Timor Lecce with all its Objectivity, personal, spatial, and temporal elements, as this court was formed to try the major perpetrators of genocide, war crimes, crimes against humanity committed since 1975 to date 10/25/1999, as well as competent to try the perpetrators of homicides, torture, sexual crimes that occurred between the date of 1/1/1999 and 10/25/1999 in the territory of East Timor, and the court consisted of international and Timorese judges, and ended its duties in 2005.
Keywords: الاختصاص القضائي الجرائم الدولية المحاكم الخاصة المحاكم المختلطة المحكمة الخاصةبتيمور الشرقية